Cannabidiol restores intestinal barrier dysfunction and inhibits the apoptotic process induced by Clostridium difficile toxin A in Caco‐2 cells. Issue 8 (1st December 2017) - Gigli, Stefano; Seguella, Luisa; Pesce, Marcella; Bruzzese, Eugenia; D'Alessandro, Alessandra; Cuomo, Rosario; Steardo, Luca; Sarnelli, Giovanni; Esposito, Giuseppe
Abstract : Background: Clostridium difficile toxin A is responsible for colonic damage observed in infected patients. Drugs able to restore Clostridium difficile toxin A‐induced toxicity have the potential to improve the recovery of infected patients. Cannabidiol is a non‐psychotropic component of Cannabis sativa, which has been demonstrated to protect enterocytes against chemical and/or inflammatory damage and to restore intestinal mucosa integrity. Objective: The purpose of this study was to evaluate (a) the anti‐apoptotic effect and (b) the mechanisms by which cannabidiol protects mucosal integrity in Caco‐2 cells exposed to Clostridium difficile toxin A. Methods: Caco‐2 cells were exposed to Clostridium difficile toxin A (30 ng/ml), with or without cannabidiol (10 −7 –10 −9  M), in the presence of the specific antagonist AM251 (10 −7  M). Cytotoxicity assay, transepithelial electrical resistence measurements, immunofluorescence analysis and immunoblot analysis were performed in the different experimental conditions. Results: Clostridium difficile toxin A significantly decreased Caco‐2 cells' viability and reduced transepithelial electrical resistence values and RhoA guanosine triphosphate (GTP), bax, zonula occludens‐1 and occludin protein expression, respectively. All these effects were significantly and concentration‐dependently inhibited by cannabidiol, whose effects were completely abolished in the presence of the cannabinoid receptor type 1 (CB1) antagonist, AM251. Conclusions: Cannabidiol improved Clostridium difficile toxin A‐induced damage in Caco‐2 cells, by inhibiting the apoptotic process and restoring the intestinal barrier integrity, through the involvement of the CB1 receptor.